Analisis Framing Pemberitaan Laga PSM Makassar Melawan Persib Bandung Pada Pembukaan Piala Presiden 2024 di Tribun-Timur.com dan TribunJabar.id - Muannas; Yusmanizar; Muhammad Yusuf AR (Jurnal Dakwah Tabligh, 2024)
This research aims to analyze the framing of news coverage by Tribun-Timur.com and TribunJabar.id and the aspects highlighted regarding the match between PSM Makassar and Persib Bandung at the opening of the 2024 President's Cup tournament. The subjects of the research are the news portals Tribun-Timur.com and TribunJabar.id. Data collection was conducted through library research and documentation. Data were analyzed using descriptive qualitative analysis employing the framing theory of Zhondang Pan and Gerald M. Kosicki, focusing on four analytical structures: syntactic, script, thematic, and rhetorical. The research results concluded that Tribun-Timur.com and TribunJabar.id framed the news of the match between PSM Makassar and Persib Bandung at the opening of the 2024 President's Cup tournament with a tendency to take sides with their respective local teams and readers. Tribun-Timur.com framed PSM Makassar's defeat as a learning and evaluation material. Tribun-Timur.com highlights the performance of the PSM Makassar team as an away team. Meanwhile, TribunJabar.id frames Persib Bandung's victory by building optimism. TribunJabar.id framed the match with a primary focus on the victory of Persib Bandung. Keywords: Framing Analysis, Tribun Timur, Tribun Jabar, Presidential Cup, PSM, Persib, Zhondang Pan and Gerald M. Kosicki